The External Quality Assurance Oversight Laboratory (EQAPOL) Proficiency Program for IFN-gamma Enzyme-Linked ImmunoSpot (IFN-γ ELISpot) assay - Sanchez, Ana M. (2014)
The Interferon-gamma Enzyme-Linked ImmunoSpot (IFN-γ ELISpot) assay has been developed and used as an end-point assay in clinical trials for infectious diseases and cancer to detect the magnitude of antigen-specific immune responses. The ability to compare data generated by different laboratories across organizations is pivotal to understand the relative potency of different therapeutic and vaccine strategies. We developed an external proficiency program for the IFN-γ ELISpot assay that evaluates the laboratory performance based on five parameters: timeliness for data reporting; ability to handle cellular samples; detection of background (non-specific) responses; accuracy to consensus of the results; and precision of the measurements. Points are awarded for each criterion, and the sum of the points is used to determine a numeric and adjectival performance rating. Importantly, the evaluation of the accuracy to the consensus mean for the detection of antigen-specific responses using laboratory-specific procedures informs each laboratory and its sponsor on the degree of concordance of its results with those obtained by other laboratories. This study will ultimately provide the scientific community with information on how to organize and implement an external proficiency program to evaluate longitudinally the performance of the participating laboratories and, therefore, fulfill the requirements of the GCLP guidelines for laboratories performing end-point IFN-γ ELISpot assay for clinical trials.